Fair Criteria of Private Vocational School and Witnesses in the Perspective of Ushul Fiqh (Analysis Based on Istislahi and Ta'lili Reasoning) - M. Jafar (Budapest International Research and Critics University, 2021)
The validity of a marriage, if it is equipped with several conditions, including a fair guardian and witnesses. This is as stated in several Hadith narrations, which clearly state that. However, in practice that is carried out by the community there is confusion regarding the fair requirements of guardians and witnesses. The proof is that all parents remain guardians in the process of their daughter's marriage and everyone can be witnesses in the marriage council. Among the scholars, there were disputes over this issue. The Ulama of the Hanafi School do not require fair guardians and witnesses in the marriage contract, even if a witness is allowed to be a man and two women. Meanwhile, for the other three schools, just guardians and witnesses in marriage are a condition for the validity of a marriage. It's just that there is a slight difference in this matter. The Ulama of the Maliki School, the two male witnesses who are just, may be presented after the marriage contract has taken place to testify that the couple is married. As for the Shafi'i School the requirements are rather strict because the fairness of guardians and witnesses must be clear inside and out. Meanwhile, according to the Hanbali School, it is a little light because the fairness of guardians and witnesses can be seen from the outside (mastur 'is). The condition for the fairness of guardians and witnesses based on istislahi theory of reasoning is to produce benefits in terms of hereditary purity. The purity of the offspring is only obtained through a marriage that is legal according to the rules of the Shari'a. The Sharia has established the validity of a marriage in between with a just guardian and witnesses. Based on the theory of ta'lili reasoning, the validity of the marriage contract is due to the existence of a just guardian and witnesses in the marriage.